2000
DOI: 10.1128/jcm.38.3.1136-1143.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Staphylococcus sciuri Strains Isolated from Humans

Abstract: We previously characterized over 100 Staphylococcus sciuri isolates, mainly of animal origin, and found that they all carried a genetic element (S. sciuri mecA) closely related to the mecA gene of methicillin-resistant Staphylococcus aureus (MRSA) strains. We also found a few isolates that carried a second copy of the gene, identical to MRSA mecA. In this work, we analyzed a collection of 28 S. sciuri strains isolated from both healthy and hospitalized individuals. This was a relatively heterogeneous group, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 27 publications
1
34
1
1
Order By: Relevance
“…In addition, PCR targeting the mecA gene as a specific marker was performed according to Couto et al. . Further details on S. sciuri W620 detection, isolation, and propagation are given in the method section of the online supplement.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PCR targeting the mecA gene as a specific marker was performed according to Couto et al. . Further details on S. sciuri W620 detection, isolation, and propagation are given in the method section of the online supplement.…”
Section: Methodsmentioning
confidence: 99%
“…The mecA gene encodes penicillin binding protein 2A, which has low affinity to β-lactam antibiotics and enables transpeptidase activities in the presence of β-lactams, thus endowing the cells with antibiotic resistance by preventing β-lactams from inhibiting cell wall synthesis (Moellering, 2011;Wu et al, 1996). Therefore, the mecA gene has been widely used as a major marker for the characterization of methicillin resistance of S. aureus strains (Corrente et al, 2007;Couto et al, 2000;Felten et al, 2002;Salisbury et al, 1997;van Duijkeren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been isolated from infections of skin and skin structures (Adegoke, ; Coimbra et al, ; Shittu, Lin, Morrison, & Kolawole, ; Stepanović, Dakić, Djukić, Lozuk, & Švabić‐Vlahović, ). Staphylococcus sciuri has also been cultured from the nares, axillae, and pharynxes of healthy individuals, hospital workers and hospitalized patients (Cirkovic et al, ; Couto, Sanches, Sa‐Leao, & de Lencastre, ), and found in the hospital setting on floors, light switches and other surfaces (Dakic et al, ). Staphylococcus sciuri has also been identified in the human genitourinary tract, including rarely in asymptomatic bacteriuria (Stepanovic et al, ) and in vaginal flora (Stepanovic et al, ).…”
mentioning
confidence: 99%